Behavior of GFRP bar reinforced geopolymer concrete filled GFRP tube columns under different loading conditions. (October 2021) - Ahmad, Junaid; Yu, Tao; Hadi, Muhammad N.S.
Abstract: This paper proposes a new type of column. The glass fiber reinforced polymer (GFRP) bar reinforced geopolymer concrete (GPC) filled GFRP tube column is presented as a potential substitute of steel reinforced ordinary Portland cement concrete (OPC) column. Type of concrete (OPC and GPC), type of longitudinal reinforcement bars (steel and GFRP) and type of transverse reinforcement (steel helix and GFRP tube) were the test parameters investigated in this study. The specimens of 200 mm diameter and 800 mm height were tested under different loading conditions. Experimental load-axial deformation, load-lateral deformation and flexural load-midspan deflection of the tested specimens are presented and discussed. An equation was also proposed for the prediction of the concentric load capacity of the column. It was found that GFRP reinforcement and GFRP tube confinement resulted in a higher ductility enhancement for GPC based specimens as compared to the OPC based specimens. Also, the ductility of GFRP bar reinforced GPC or OPC filled GFRP tube columns increased with the load eccentricity. Whereas, the ductility of the steel reinforced specimens decreased with the increase of load eccentricity.